Wastewater analysis for psychoactive substances at music festivals across New South Wales, Australia in 2019–2020. (3rd April 2022) - Brett, Jonathan; Siefried, Krista J.; Healey, Amy; Harrod, Mary Ellen; Franklin, Erica; Barratt, Monica J.; Masters, Jem; Nguyen, Lynn; Adiraju, Santosh; Gerber, Cobus
Abstract: Introduction: Implementation of wastewater surveillance at music festivals has been limited to date. We aimed to use wastewater analysis and a self-report survey to determine the range of psychoactive substances being used during a music festival season in New South Wales, Australia. Methods: We sampled six single-day music festivals requiring a music festival license in New South Wales from March 2019 to March 2020; between 15% and 100% of portaloos (temporary, un-fixed toilet facilities) were sampled at each festival. Samples were screened for 98 psychoactive substances and/or their metabolites with results qualitatively expressed as detection frequencies for each substance at each festival and across all festivals. We compared these data with the results of surveys of self-reported drug use at four of the six festivals. Results: Festival attendance ranged from 6200 to 14, 975 people. Amphetamine, cocaine, ketamine, methylone, MDMA, MDA, alprazolam, diazepam, etizolam, oxazepam and temazepam were found in almost all samples from all festivals. Ethylone, mephedrone and methcathinone were also found in over 50% of festivals. A norfentanyl (a fentanyl metabolite) and n-ethylpentylone were found at 2/6 and 1/6 festivals. No festival survey participant reported intentionally taking cathinones. Discussion: The detection frequency for cathinones was higher than expected relative to recent other data sources and this may represent adulteration or substitution. Similarly, the appearance of etizolam may be related to the use of counterfeit alprazolam. The detection of highly toxic substances such as N-ethylpentylone and norfentanyl may warrant public health alerts. Conclusion: If provided close to real time, wastewater analysis at festivals could be complemented with information sources such as drug checking, on-site surveys, medical presentations and intelligence from peer networks to feed into early warning systems, public health alerts and peer-based harm reduction education during the festival season.